Diagnostic accuracy of cytology for the detection of endometrial cancer in urine and vaginal samples - Helena O’Flynn (Nature Portfolio, 2021)
Postmenopausal bleeding can be an indication of endometrial cancer. Here, the authors combine cytology of urine and vaginal samples from women with postmenopausal bleeding and demonstrate that they can accurately predict endometrial cancer with a sensitivity of 91.7% and specificity of 88.8%.